Modelado y Simulación de un Robot Terapéutico para la Rehabilitación de Miembros Inferiores. - Humberto Guzmán Valdivia, César; Blanco Ortega, Andrés; Antonio Oliver Salazar, Marco; Ramón Azcaray Rivera, Héctor (Biomedical Engineering Journal / Revista Ingeniería Biomédica)
Rehabilitation in a general sense aims to reinstate a person to their activities of daily living. Currently, a patient that requires a rehabilitation suffers long waits for treatment due to lack of staff in clinics and hospitals. An alternative to assist medical staff in rehabilitation therapies is using therapeutic robots. This paper shows the modeling and simulation of a therapeutic robot for lower limb rehabilitation. The kinematic and dynamic model of a robot of three degrees of freedom with an end-effector configured in parallel is presented. A computed torque control law for a planned trajectory tracking task is presented. Simulations of therapeutic exercises for hip and knee carried out in ADAMS and MATLAB for know the kinematic and dynamic behavior of the robot are presented. The results demonstrate the great potential of the therapeutic robot to assist in the rehabilitation of lower limbs.